The Hawkish Dove: Evolution and the Logic of Political Behaviour. (September 2014) - Lopez, Anthony C.
In a previous issue of this journal, Adam Goodwin (2010) argued that applications of 'orthodox' evolutionary theory in international relations are reductionist, necessarily privilege an individualist ontology, and doom social theorising to the false assumption that humans are by nature selfish and competitive. As an alternative, Goodwin presents Kropotkin's Mutual Aid framework both for overcoming the reductionism of 'orthodox' evolutionary theory and for establishing a holist ontology cantered around the autonomy of social forms. I argue that Goodwin's representation of 'orthodox' evolutionary theory is in fact far from orthodoxy and instead rests on misunderstandings both of how natural selection operates and what it operates to produce – adaptations. I show that modern evolutionary theory rests on neither individualist nor holist ontologies, and instead demonstrates that humans are by nature neither hawkish nor dovish. I provide examples on the evolution of cooperation and war to demonstrate that modern evolutionary theory can explain a range of pro- and anti-social behaviours and that fears of biological reductionism in international relations are misplaced.